2013
DOI: 10.1002/hbm.22271
|View full text |Cite
|
Sign up to set email alerts
|

Callosal degeneration topographically correlated with cognitive function in amnestic mild cognitive impairment and alzheimer's disease dementia

Abstract: Degeneration of the corpus callosum (CC) is evident in the pathogenesis of Alzheimer's disease (AD). However, the correlation of microstructural damage in the CC on the cognitive performance of patients with amnestic mild cognitive impairment (aMCI) and AD dementia is undetermined. We enrolled 26 normal controls, 24 patients with AD dementia, and 40 single-domain aMCI patients with at least grade 1 hippocampal atrophy and isolated memory impairment. Diffusion tensor imaging (DTI) with fractional anisotropy (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…A prominent involvement of temporoparietal regions and, to a lesser extent, the frontal lobes has been detected by both region of interest [35,36,37,38] and voxel-based DT MRI studies [39,40,41,42]. Tractography studies in AD showed the presence of diffusion abnormalities in the major limbic tracts, such as the fornix [43,44] and cingulum [45,46], and corticocortical association tracts, such as the corpus callosum (CC) [43,45,47], uncinate [43,45,48], inferior fronto-occipital [43,49], superior longitudinal [43] and inferior longitudinal [43] fasciculi. An increased radial diffusivity is commonly found in AD involving temporal, frontal and parietal regions [42,50] while less consistent results are reported for axial diffusivity [40,41,51,52].…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…A prominent involvement of temporoparietal regions and, to a lesser extent, the frontal lobes has been detected by both region of interest [35,36,37,38] and voxel-based DT MRI studies [39,40,41,42]. Tractography studies in AD showed the presence of diffusion abnormalities in the major limbic tracts, such as the fornix [43,44] and cingulum [45,46], and corticocortical association tracts, such as the corpus callosum (CC) [43,45,47], uncinate [43,45,48], inferior fronto-occipital [43,49], superior longitudinal [43] and inferior longitudinal [43] fasciculi. An increased radial diffusivity is commonly found in AD involving temporal, frontal and parietal regions [42,50] while less consistent results are reported for axial diffusivity [40,41,51,52].…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…All image data analyses and parcellations of the CC were performed as previously described in detail [18].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce eddy current distortions and motion artifacts, each diffusion-weighted image was registered to the non-diffusion weighted image by an affine registration approach that was supplied in FMRIB's Linear Image Registration Tool. We then used the Brain Extraction Tool to strip the skull from the non-diffusion weighted image and from the corresponding T1-weighted image of each participant to remove non-brain tissue and background noise from the images, ensuring the accuracy of cross-modality image registration [17,18].…”
Section: Data Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations